Seismic Monitoring System of Baixo Sabor and Feiticeiro Dams - Monteiro, Gilberto Silva; Neves, Jorge Pacheco; Gomes, Jorge Pereira (Salehan Institute of Higher Education, 2020)
In the last decade Portugal made a significant set of investments in new hydroelectric projects. According the Portuguese Dam Safety Regulation and Supporting Technical Documents, and the seismic risk for the regions where the dams were built, several seismic monitoring systems were implemented. One of the most important projects was the Baixo Sabor hydroelectric scheme which includes two large dams, namely the Baixo Sabor and Feiticeiro dams. These dams are located at northeast of Portugal and are very close to a major geological fault that crosses the Portuguese territory. Considering the seismic risk of the damâ€™s construction area, a seismic monitoring system was provided. That system incorporates stations in the damâ€™s galleries and remote stations along the reservoirs to detect eventual induced reservoir seismicity. This system has been in continuous operation and the data of the recorded earthquakes records has been analyzed and processed. This paper presents some aspects of the Portuguese legislation, refers the main studies that were used, presents a brief description of the regional Baixo Sabor geological and tectonic settings, describes the main features of the seismic monitoring system and presents some of the main results obtained during the first period of operation of the dams.Â Doi: 10.28991/cej-2020-03091603 Full Text: PDF